Streptococcus sanguinis as an opportunistic bacteria in human oral cavity: Adherence, colonization, and invasion - Pramesti, Hening Tjaturina (Padjadjaran Journal of Dentistry, 2016)
Streptococcus sanguinis (formerly S. sanguis) is a Gram-positive, facultative anaerobe,  nonmotile , normal  inhabitant of the human oral cavity, and  a member of  the viridans group of streptococci. Among the streptococcus, S. sanguinis is a  primary colonizer in the human tooth surface or it is recognize as a ‘pioneer’ by forming dental plaque. The aim of this paper is to review the role of Streptococcus sanguinis  in the adherence to and  invasion of  human tissues.  S. sanguinis  has been reported  that it is associated  with healthy  tooth  surfaces  but not with caries. S. sanguinis  tend to involved in an interspecies interactions with Streptococcus mutans, which is known as  competition/coexistence within dental biofilm.  In their colonization, this bacteria used enzyme sortase A (SrtA) to cleave  LPXTG-containing proteins sequence and  anchored  the  cell wall, while virulence factors  in infective endocarditis  involved housekeeping functions such as cell wall synthesis, amino acid and nucleic acid synthesis, and the ability to survive under anaerobic conditions.